Point Prevalence of Complementary or Alternative Medicine Use among Children Attending a Tertiary Care Hospital - Angharad Vernon-Roberts; Abida Denny; Andrew S. Day (MDPI AG, 2023)
Background: Complementary or alternative medicine (CAM) describes products/practices outside conventional medical care. CAM may be used to support or replace conventional/prescribed therapies. The aim of this study was to determine patterns of CAM use among children attending a tertiary care hospital in New Zealand (NZ) and measure parental opinion about CAM. Methods: Prospective survey-based study among children and their parents attending inpatient and outpatient clinical areas. Surveys collected demographic and health variables, current CAM use, and parental opinions on CAM. Results: Of the 236 children participating: 41% female, mean age 6.8 years (SD5), 76 (32%) with a chronic illness. CAM was used by 132 (56%) children, the most common being: oral supplements, body manipulation methods, or holistic practices. CAM use was associated with lower child health rating (p = 0.001), Māori ethnicity (p = 0.03), parent education level (p = 0.002), and family member CAM use (p < 0.001). Opinion survey results revealed CAM use was most strongly related to doctors recommending CAM, information on CAM, and CAM cost. There was a 31% CAM disclosure rate to the child's medical team. Conclusions: This study highlights cultural differences in CAM use not previously reported among children in NZ. Parental opinion regarding CAM influences use for their child and disclosure rates.